A functional characteristic of cysteine‐rich protein 61: Modulation of myeloid‐derived suppressor cells in liver inflammation. Issue 1 (17th November 2017) - Zhang, Haiyan; Lian, Min; Zhang, Jun; Bian, Zhaolian; Tang, Ruqi; Miao, Qi; Peng, Yanshen; Fang, Jingyuan; You, Zhengrui; Invernizzi, Pietro; Wang, Qixia; Gershwin, M. Eric; et al.
Abstract : There is increasing awareness of the immunologic roles of liver mononuclear populations, including myeloid‐derived suppressor cells (MDSCs). We took advantage of a large well‐defined cohort of 148 patients with liver inflammation and 45 healthy controls to focus on the qualitative and quantitative characteristics of MDSCs. We investigated the frequency, phenotype, and functional capacities of MDSCs by using peripheral blood MDSCs in a cohort of 55 patients with primary biliary cholangitis (PBC), 40 with autoimmune hepatitis, 39 with chronic hepatitis B, 14 with nonalcoholic fatty liver disease, and 45 healthy controls. This was followed by a liver‐targeted determination in 27 patients with PBC, 27 with autoimmune hepatitis, 20 with chronic hepatitis B, 14 with nonalcoholic fatty liver disease, and 6 controls. We then focused on mechanisms of this expansion with PBC as an example, using both ursodeoxycholic acid‐naive and treated patients. HLA‐DR −/low CD33 + CD11b + CD14 + CD15 − monocytic MDSCs were elevated in diseases characterized by liver inflammation compared to healthy controls. Using PBC as a focus, there was a significant correlation between levels of circulating MDSCs and disease‐related biochemical markers (alkaline phosphatase, total bilirubin). We found higher amounts of MDSCs in patients with PBC who were responsive to ursodeoxycholic acid. MDSCs from PBC were found to manifest a potent immunosuppressive function. There was a significant correlation in the accumulation of hepatic MDSCs in the inflamed lesions of PBC with histologic changes, such as fibrosis. We also found that cysteine‐rich protein 61 (CCN1), a highly expressed protein in impaired cholangiocytes and hepatocytes, contributes to MDSC expansion and MDSC inducible nitric oxide synthase‐associated immune suppression. Conclusion : CCN1 modulates expansion and a suppressive function of MDSCs. Our data highlight the potential functions of CCN1 on MDSCs and suggest therapeutic implications in inflammatory liver diseases. (Hepatology HEPATOLOGY 2018;67:232‐246).